Experimental study on an airfoil equipped with an active flow control element. Issue 4 (August 2022) - Hochhäusler, Dominik; Erfort, Gareth
This paper addresses the torque ripple problem of vertical axis wind turbines (VAWT) by applying an oscillating bump which was previously optimised with a numerical model. Since the element primarily affects the drag of an airfoil, a low-speed wind-tunnel experiment using the wake survey method was conducted in order to highlight the effect on the drag of a symmetrical airfoil. Measurements were taken along the centreline of the foil to compare with numerically simulated results on a 2D foil. This study provides an experimental data set for an active flow control device. When the stationary results were compared against numerical simulation they showed an overall good agreement. The moving bump increased the drag coefficient for higher frequencies of oscillation and induced less drag compared to the steady maximum distortion. Uncertainties in the experiments were primarily caused by fluctuations in the test section and the data reduction error. Future work should include the measurement of lift in order to determine the influence of the element on the torque.